Mengukur kinerja karyawan dengan nilai spritualitas sebagai moderasi - Adhi Pratama, Putra; Fitriyani, Endah Nur (Journal of Management and Digital Business, 2022)
This study aims to determine the effect of work climate, motivation, and sense of community on employee performance with spirituality as a moderating variable. This type of research is a quantitative study with a population of all PDAM Purwa Tirta Dharma Grobogan employees. The number of samples is 66 respondents. The analytical method used is Moderated Regression Analysis. The study results show that the work climate, motivation, and sense of community positively affect employee performance. Work atmosphere and sense of community partially positively affect employee performance, while motivation has no effect. Spirituality can moderate (strengthen) the influence of work climate variables, motivation, and sense of community on employee performance.